Cold War on CNN, Part 10: Cuba 1959-1962 (Jeremy Isaacs Productions, 1998)
In the 1960s the United States claimed its place as the world's leading defender against communism. But by the end of the decade, the nation was convulsed by dissent, riot, assassination and an increasingly unpopular war.